A Portable Laboratory Kit for Student Self-Learning on Factors That Affect Reactions - Tuszie Widhiyanti; Jihan Assyifa Fatihah; Sri Mulyani; Wiji Wiji (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
In chemistry practicums, students can enhance their scientific thinking skills and develop scientific attitudes. However, in some underprivileged schools, particularly during the COVID-19 pandemic, practicum activities were restricted due to the unavailability of laboratory tools and materials. To address this issue, a portable laboratory kit was developed to support practical learning experiences. This study aims to develop a portable laboratory tool model, integrating the Predict-Observe-Explain (POE) approach, to improve students' learning outcomes on reaction rates. This research employs a mixed-methods approach with an embedded experimental model, utilizing a one-group pretest-posttest design. The portable laboratory kit includes hands-on tools and materials, student worksheets, and teacher guides aligned with POE learning syntax. Three experts conducted validation and implementation involving 24 high school students. A novelty of this study lies in the practical worksheet design, which follows the POE learning syntax and fosters intertextual relationships across macroscopic, submicroscopic, and symbolic representations. The findings reveal a significant difference between pretest and posttest scores regarding students' understanding of factors affecting reaction rates. Specifically, the number of students who demonstrated complete understanding after the intervention was: nine for the effect of structure on reaction rate, 13 for the effect of ionization energy on reaction rate, and 20 for the effect of surface area on reaction rate. Regarding catalysts, 15 students fully understood the effect of a homogeneous catalyst, and 18 students understood the effect of a heterogeneous catalyst. Interviews with teachers and students further indicated that students found the approach novel, motivating them to engage more deeply. Additionally, many students expressed feeling particularly challenged during the prediction stage of the POE learning process.